RANCANG BANGUN PROTOTYPE CAT FEEDER (SMART – CAT) BERBASIS IOT - Zendate, Sabar Serius; Sunarsan Sitohang (Computer Science and Industrial Engineering, 2024)
New opportunities to automate everyday devices such as pet feeding have emerged as a result of the use of the Internet of Things (IoT). The focus of this research is the development of an Internet of Things-based Cat Feeder that utilizes the Blynk platform, Kodular, and sensors. Blynk enables remote cat feeding settings through an application that has an easy-to-use interface. Kodular is used as a visual application development platform in this research, allowing application creators who do not have a deep programming background to easily create user interfaces. Sensors integrated in the system collect data on the cat's behavior and diet. This allows owners to better monitor and manage their cat's diet. During the development process, Blynk was used to incorporate remote control, Kodular was used to create the user interface, and sensors were used as data input. The results show that this solution makes feeding cats easier and gives owners better control over the amount of food their pets consume. The no-code/low-code approach used in the development of the app is an advantage of this research as it allows the app to be more accessible to a wide range of users. By using sensors, cat health can be better monitored and owners can better manage their cat's food needs.